Multi-layered interbank model for assessing systemic risk - Mattia Montagna; Christoffer Kok (European Central Bank (ECB), 2016)
In this paper, we develop an agent-based multi-layered interbank network model based on a sample of large EU banks. The model allows for taking a more holistic approach to interbank contagion than is standard in the literature. A key finding of the paper is that there are material non-linearities in the propagation of shocks to individual banks when taking into account that banks are related to each other in various market segments. The contagion effects when considering the shock propagation simultaneously across multiple layers of interbank networks can be substantially larger than the sum of the contagion-induced losses when considering the network layers individually. In addition, a bank “systemic importance” measure based on the multi-layered network model is developed and is shown to outperform standard network centrality indicators. The finding of non-linear contagion effects when accounting for the interaction between the different layers of banks' interlinkages have important policy implications. For example, it provides an argument for separating banks' trading activities from their other intermediation activities.
Keywords: C45; C63; D85; G21; 330; Financial contagion; interbank market; network theory